Use of antiretrovirals in pregnant women living with HIV in Brazil: A retrospective cohort, 2014-2019 (Research, Society and Development, 2025)
HIV cases in Brazilian women primarily occur during their reproductive years, with increasing detection rates among pregnant women in recent years. Changes in antiretroviral therapy (ART) protocols have influenced the management of pregnant women living with HIV (PWLHIV). Objective: To evaluate the use of antiretrovirals (ARVs) and the sociodemographic profile of PWLHIV in Brazil between 2014 and 2019. Methods: A retrospective cohort study was conducted using data from the Drug Logistics Control System (SICLOM). Women aged 14 years or older with at least one ARV dispensation during pregnancy were included. Pregnant women were categorized as those with prior ART use or those initiating ART during pregnancy. Descriptive and analytical statistics were applied. Results: The study included 34,659 pregnant women: 53.3% had prior ART use, and 46.7% initiated ART during pregnancy. Most were aged 30-39 years (32.6%), non-white (46.7%), without a partner (38.5%), and had 8-11 years of education (27.7%). The mean ART duration was 174.2 days, with adverse drug reactions reported by 14.3%. ARV regimens evolved during the study period, with lopinavir + ritonavir/zidovudine + lamivudine used until 2016, tenofovir + lamivudine + efavirenz in 2017, and tenofovir + lamivudine/raltegravir from 2018 onwards. Conclusion: ART use among PWLHIV aligned with national protocols, reflecting consistent practices. However, the findings highlight social vulnerabilities and the need for improved access to healthcare. Enhancing reproductive health services in Brazil remains essential to reduce vertical transmission and ensure comprehensive care.